The ”People’s home” is falling down, time to update your view of Sweden (Sociologisk Forskning, 2017)
Swedish society is changing profoundly. The egalitarian, solidaristic ”People’s Home”, which has attracted widespread progressive admiration internationally, is being eroded and dismantled. The political economy of this process, since the turn of the l980s, is highlighted; a process which includes a major, if not complete, substitution of a capitalist market of social provision for a welfare state, and of a stock market-driven capitalism for a full employment work economy. Some of its direct inegalitarian consequences are indicated, as well as unintended ones of petty corruption, cronyism, and swindle. The socio-political dynamics of the turn is briefly outlined.